Red blood cells serve as intravascular carriers of myeloperoxidase - Adam, Matti; Gajdova, Silvie; Kolarova, Hana; Kubala, Lukas; Lau, Denise; Geisler, Anne; Ravekes, Thorben; Rudolph, Volker; Tsao, Philip S; Blankenberg, Stefan; Baldus, Stephan; Klinke, Anna (Journal of Molecular and Cellular Cardiology, 2014)
Myeloperoxidase (MPO) is a heme enzyme abundantly expressed in polymorphonuclear neutrophils. MPO is enzymatically capable of catalyzing the generation of reactive oxygen species (ROS) and the consumption of nitric oxide (NO). Thus MPO has both potent microbicidal and, upon binding to the vessel wall, pro-inflammatory properties. Interestingly, MPO - a highly cationic protein - has been shown to bind to both endothelial cells and leukocyte membranes. Given the anionic surface charge of red blood cells, we investigated binding of MPO to erythrocytes. Red blood cells (RBCs) derived from patients with elevated MPO plasma levels showed significantly higher amounts of MPO by flow cytometry and ELISA than healthy controls. Heparin-induced MPO-release from patient-derived RBCs was significantly increased compared to controls. Ex vivo experiments revealed dose and time dependency for MPO-RBC binding, and immunofluorescence staining as well as confocal microscopy localized MPO-RBC interaction to the erythrocyte plasma membrane. NO-consumption by RBC-membrane fragments (erythrocyte "ghosts") increased with incrementally greater concentrations of MPO during incubation, indicating preserved catalytic MPO activity. In vivo infusion of MPO-loaded RBCs into C57BL/6J mice increased local MPO tissue concentrations in liver, spleen, lung, and heart tissue as well as within the cardiac vasculature. Further, NO-dependent relaxation of aortic rings was altered by RBC bound-MPO and systemic vascular resistance significantly increased after infusion of MPO-loaded RBCs into mice. In summary, we find that MPO binds to RBC membranes in vitro and in vivo, is transported by RBCs to remote sites in mice, and affects endothelial function as well as systemic vascular resistance. RBCs may avidly bind circulating MPO, and act as carriers of this leukocyte-derived enzyme.
Keywords: Nitric Oxide; Protein Binding; Heparin; aorta; peroxidasa; Male; orgánové kultury - kultivační techniky; srdeční selhání; cévní endotel; cévní rezistence; srdce; akutní koronární syndrom; Peroxidase; oxid dusnatý; mužské pohlaví; Endothelium, Vascular; Organ Culture Techniques; techniky tkáňových kultur; Aorta; kultivované buňky; vazba proteinů; biologický transport; Acute Coronary Syndrome; Animals; lidé; Heart Failure; Humans; zvířata; Vascular Resistance; myši inbrední C57BL; erytrocyty; myši; Erythrocytes; Mice, Inbred C57BL; Cells, Cultured; Mice; Heart; heparin; Biological Transport; Tissue Culture Techniques